PENGARUH KECERDASAN EMOSIONAL DAN KECERDASAN INTELEKTUAL TERHADAP KINERJA GURU SMA NEGERI 1 PULAU MAKIAN - Ilham Mursal; Nurlaila Nurlaila (Jurnal Manajemen Sinergi, 2017)
This study aims to determine the effect of emosional intelligence and intellectual intelligence on teacher performance. The study was conduted in SMA Negeri 1 Pulau Makian.As for the respondents used in this study were 35 respondents, with respondents make in use of techniques population and using multiple regression analysis.The result showed that emotional intelligence either partially or simultaneously positive and significant impact on teacher performance in SMA Negeri 1 Pulau Makian.